Evaluation of Public Service Networks' Efficiency and Accessibility Levels in Urban Areas - Yorgos Photis; Fotini Athanasiou (European Regional Science Association (ERSA), 2006)
Trips in urban areas from residence to different activities constitute a large amount of daily transportations. The study of these trips and especially those towards public sector services and by public transportation means is essential in order to evaluate the effectiveness of public networks planning. In this paper, both public services and public buses networks are studied in a joint framework in order to evaluate their spatial allocation association which reflects effective service of citizens' daily trips. The proposed methodology utilizes GIS technology and spatial analysis methods and is applied to the city of Volos (Greece). In this framework, population of each building block is assigned to the closest bus station (destination) while each bus station (origin) is assigned to its closest public facility. Different service areas are defined for each station and public service and the proximity of all building blocks is calculated. Further processing of the resulting information leads to the quantification of the spatial relationship between demand (population) and supply (public services and bus stations) and therefore, to the evaluation of the efficiency and effectiveness levels of public networks in urban areas.
Keywords: 330